Nikolai Chernyshevskii and Ayn Rand : Russian nihilism travels to America - Weinacht, Aaron, 1977- (Lanham: Lexington Books, 2021)
"Nikolai Chernyshevskii and Ayn Rand: Russian Nihilism Travels to America argues that the core commitments of the 1860's nihilism made their way to 20th century America via the thought of Ayn Rand. Nikolai Chernyshevskii's What is to Be Done? (1863) and Rand's Atlas Shrugged (1957) identify similar problems; identical theses propose to solve those problems"--
Includes bibliographical references and index.
Keywords: Rand, Ayn; Chernyshevsky, Nikolay Gavrilovich, -- 1828-1889 -- Influence; Chernyshevsky, Nikolay Gavrilovich, -- 1828-1889.; Rand, Ayn -- Philosophy; Nihilism in literature; Russian literature -- 19th century -- History and criticism; Objectivism (Philosophy); Literary criticism